Effect of Crude Palm Oil and Waste Cooking Oil Blend Composition and Stirring Speed on Biodiesel Yield During Transesterification Using KOH Catalyst - Yoggie Alvianito; Yohandri Bow; Sahrul Effendy A (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
The growing demand for energy and the depletion of fossil fuel reserves have accelerated the development of renewable energy sources. Biodiesel has emerged as a promising alternative because it can be produced from renewable feedstocks while reducing environmental impacts. This study investigated the effects of the composition of the crude palm oil (CPO) and waste cooking oil (WCO) blend, as well as stirring speed, on biodiesel yield and fuel properties during alkaline transesterification using a potassium hydroxide (KOH) catalyst. Five feedstock compositions consisting of 100:0, 75:25, 50:50, 25:75, and 0:100 (CPO:WCO) were evaluated at stirring speeds of 400 and 600 rpm. The transesterification process was carried out at 60°C for 60 min using a methanol to oil molar ratio of 6:1 and 1 wt.% KOH catalyst. Biodiesel products were characterized based on yield, density, kinematic viscosity, acid value, calorific value, cetane number, and fatty acid methyl ester (FAME) composition using gas chromatography mass spectrometry (GC-MS). The results demonstrated that both feedstock composition and stirring speed significantly affected biodiesel production. Increasing the proportion of waste cooking oil improved biodiesel yield, while increasing stirring speed enhanced mass transfer between methanol and oil, leading to higher conversion efficiency. The highest biodiesel yield of 80% was obtained at a CPO:WCO ratio of 25:75 with a stirring speed of 600 rpm. The produced biodiesel exhibited density, viscosity, acid value, calorific value, and cetane number within the requirements of the Indonesian National Standard (SNI 7182:2015). GC-MS analysis confirmed a FAME content of 79.18%, indicating effective transesterification. These findings demonstrate that optimizing feedstock composition and mixing intensity can improve biodiesel production efficiency while promoting the utilization of waste cooking oil as a sustainable renewable energy resource. Contribution to Sustainable Development Goals (SDGs):SDG 7: Affordable and Clean EnergySDG 12: Responsible Consumption and ProductionSDG 13: Climate Action